PERENCANAAN DRAINASE ARENA PACUAN KUDA ANGIN LAUT DESA PENYARING KECAMATAN MOYO UTARA - Fajri, Nur; Satriawansyah, Tri; Nuraini, Eni; Padusung; Lamo, Ahmad (Jurnal SainTekA, 2021)
The sea breeze horse racing arena located in Penyaring Village, North Moyo District, when it rains, will always be flooded because there are no channels that can drain and catch rainwater on the racetrack. So it is necessary to plan a drainage channel in the sea breeze racetrack as a solution to the arena. The purpose of this study 1). to find out the design discharge of the sea breeze racetrack drainage channel, 2). To find out how the dimensions of the drainage of the sea breeze racetrack, 3). To find out the impact of planning the drainage of the sea breeze racetrack.The data or information used is secondary data obtained from the Central Statistics Agency of Sumbawa Regency and primary data is obtained from direct surveys in the field. The method used in determining the maximum rainfall is the Gumbel Method.After doing the calculation, the researcher gets (1). From the results of the analysis, to determine the planned discharge using 10 years of rainfall data at the stations of North Moyo District, Moyo Hilir District and Sumbawa District and the plan return period is 10 years. Based on the calculation, it is obtained that the total planned discharge is Q runoff = 3,199 m3/second, (2). The dimensions of the channel use a trapezoidal cross section with a slope of 0.7 m. base width (B) = 0.6 m, water level (h) = 0.7 m and guard height (w) = 0.8 m, (3). The results of the calculation of the capacity of the reservoir, the capacity of the reservoir A = 1047.22 M3, the capacity of the reservoir B = 1022.14 M3 the capacity of the reservoir C = 543.96 M3